Characterization of NO2 Emissions in the Sichuan Basin based on TROPOMI Data - Xianyu YANG; Bingzheng BEN; Yaqiong LÜ; Song WANG; Wenlei WANG; Qin HU; Jun WEN; Tong YANG; Ziyi WANG; Meixia LI (Gaoyuan qixiang)
This study utilizes a high-resolution emission inventory and the WRF-CMAQ modeling system to analyze the temporal and spatial evolution of tropospheric NO₂ vertical column density （VCD） derived from TROPOMI satellite data. It also provides a preliminary assessment of the uncertainty in the NOₓ emission inventory for the Sichuan Basin in 2019. The findings reveal elevated tropospheric NO₂ VCD in areas with intense anthropogenic activity， including the Chengdu Plain， southern Sichuan's urban clusters， and Chongqing， while the central Sichuan Basin remains relatively clean. Seasonal variations， influenced by both meteorological conditions and anthropogenic emissions， show significantly higher NO₂ VCD in winter and spring compared to summer and autumn. A comparison between the WRF-CMAQ model and TROPOMI satellite data for January 2019 indicates strong agreement in cleaner regions， though TROPOMI reports notably higher NO₂ VCD in high-emission cities such as Chengdu and Chongqing， suggesting that the emission inventory may underestimate NOₓ emissions in megacities. This work underscores the need for stringent NOₓ emission controls in major cities， such as Chengdu and Chongqing， while also emphasizing the urgency of enhancing emission controls in medium-sized cities across the Sichuan Basin.